Risk Management of Neuroanesthesia in Traumatic Brain Injury with Multiple Facial Fractures and Subcutaneous Emphysema in terms of Ethical and Medicolegal Aspects - Kulsum; Taufik Suryadi (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Every medical practice including neuroanesthesia always contains risks, so risk management is needed. Neuroanesthesia in cases of traumatic brain injury (TBI) with multiple facial fractures and subcutaneous emphysema is one of the risky prosedure that must be done very carefully and professionally. A case reported by a man, 53 years old, weight 80 kg, decreased consciousness due to head trauma and facial trauma and the presence of widespread subcutaneous emphysema. Performed risk management in the form of airway management, installation of water seal drainage and perioperative neuroanesthesia aimed at reducing intracranial pressure and maintaining adequate cerebral perfusion pressure. Medical decision making in this case does not only give attention to medical aspects but also must give attention to aspects of clinical ethics and medico-legal. Criteria for TBI patients with multiple facial fractures and subcutaneous emphysema for neuroanesthesia based on ethical and medicolegal considerations can be carried out based on clinical ethics theory and neuroanesthesia risk management so as to produce good patient outcomes.